Light scattering and random lasing in aqueous suspensions of hexagonal boron nitride nanoflakes. (26th October 2017) - O'Brien, S A; Harvey, A; Griffin, A; Donnelly, T; Mulcahy, D; Coleman, J N; Donegan, J F; McCloskey, D
Abstract: Liquid phase exfoliation allows large scale production of 2D materials in solution. The particles are highly anisotropic and strongly scatter light. While spherical particles can be accurately and precisely described by a single parameter—the radius, 2D nanoflakes, however, cannot be so easily described. We investigate light scattering in aqueous solutions of 2D hexagonal boron nitride nanoflakes in the single and multiple scattering regimes. In the single scattering regime, the anisotropic 2D materials show a much stronger depolarization of light when compared to spherical particles of similar size. In the multiple scattering regime, the scattering as a function of optical path for hexagonal boron nitride nanoflakes of a given lateral length was found to be qualitatively equivalent to scattering from spheres with the same diameter. We also report the presence of random lasing in high concentration suspensions of aqueous h-BN mixed with Rhodamine B dye. The h-BN works as a scattering agent and Rhodamine B as a gain medium for the process. We observed random lasing at 587 nm with a threshold energy of 0.8 mJ.